Association between 318C/T polymorphism of the CTLA‐4 gene and systemic lupus erythematosus in Iranian patients. (9th January 2014) - Shojaa, Mahdieh; Aghaie, Mehrdad; Amoli, Mahsa; Javid, Naemeh; Shakeri, Fatemeh; Khashayar, Patricia; Tabarraei, Alijan; Keshtkar, Abbas A.; Joshaghani, Hamid R.; Kouroshnia, Arghavan; Qorbani, Mostafa; Mahmoudi, Faranak; et al.
Abstract: Background: Cytotoxic T lymphocyte‐associated antigen‐4 ( CTLA‐4 ) is an important negative regulator of T‐cell response. It is a functional candidate gene connected with susceptibility to systemic lupus erythematosus (SLE). We analyzed the role of −318C/T polymorphism in the promoter region of the CTLA‐4 gene in Iranian patients suffering from SLE. Methods: A total of 180 SLE patients and 304 healthy ethnically matched controls were enrolled in the study. DNA was extracted from blood samples according to the standard procedure. Polymerase chain reaction restriction fragments length polymorphism (PCR‐RFLP) was used to analyze the genotype and allele frequencies of these polymorphisms. Results: The CC genotype was observed in 170 (94.5%) of the SLE patients, which was significantly different compared to the controls (251 [82.4%]; P = 0.0001, OR = 3.51 95%CI = 1.77–7.53). T allele was significantly more common in the controls (9.2%) compared to SLE patients 2.8% ( P = 0.0001, OR = 0.26, 95%CI = 0.13–0.53). There was no significant correlation between different genotypes and age, gender or family history of SLE in the studied population. Conclusion: It can be concluded that −318C/T polymorphism of CTLA‐4 gene might play a significant role in the development of SLE in the Iranian patients.